PENGARUH RASIO NILAI PASAR DAN PROFITABILITAS TERHADAP HARGA DAN RETURN SAHAM PERBANKAN YANG TERDAFTAR DI BEI PADA MASA PANDEMI COVID-19 - Mitha Icha Yanti Tambun; Agung Dharmawan Buchdadi; M. Edo Suryawan Siregar (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This study aims to test whether there is an effect of market value and profitability ratios on the prices and returns of banking shares listed on the IDX during the COVID-19 pandemic (2020–2022). The Market Value Ratio is proxied by Dividend Per Share (DPS) and Earning Per Share (EPS). Meanwhile, the profitability ratio is proxied by Return on Investment (ROI). This research uses 12 financial companies listed on the IDX as research samples. The sampling method used was a purposive sampling technique. The analysis technique used is panel data regression. This research also uses an additional sample, namely in the period before the COVID-19 pandemic (2017–2019) as a comparison. The research results show that DPS and EPS have a positive and significant effect on share prices during the COVID-19 pandemic, but have no effect on stock returns. Then, ROI has no effect on stock prices during the pre-pandemic period or during the COVID-19 pandemic, but it does affect stock returns.